2016
DOI: 10.1002/iid3.97
|View full text |Cite
|
Sign up to set email alerts
|

Acute hyperglycemia impairs IL‐6 expression in humans

Abstract: Normal glucose metabolism is critical to immune function but the effects of short‐term hyperglycemia on immunity are not well described. To study this phenomenon, we induced hyperglycemia in healthy subjects for 2 h with intravenous dextrose and octreotide. An RNA‐seq analysis of whole blood RNA demonstrated alterations in multiple immune pathways and transcripts during acute hyperglycemia including decreased transcription of IL‐6, an important component of both innate and adaptive immune responses. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…PBMC from healthy individuals with induced hyperglycemia of two hours duration showed decreased transcription of IL-6 and IL-17. Similar findings were obtained following incubation of monocytes with high glucose levels [24]. It has been reported that feeding induces an increase in the number of peritoneal macrophages secreting IL-1β and that this cytokine is closely connected with the uptake of glucose into the cells [25].…”
Section: Discussionsupporting
confidence: 80%
“…PBMC from healthy individuals with induced hyperglycemia of two hours duration showed decreased transcription of IL-6 and IL-17. Similar findings were obtained following incubation of monocytes with high glucose levels [24]. It has been reported that feeding induces an increase in the number of peritoneal macrophages secreting IL-1β and that this cytokine is closely connected with the uptake of glucose into the cells [25].…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, Spindler et al . reported that PBMCs obtained from healthy subjects and induced with dextrose octreotide demonstrated reduced IL-6 and IL-17A expression, especially in CD14+ and CD16+ intermediate monocytes, indicating impaired immune responses due to high blood glucose levels [ 51 ]. Another study conducted by Price et al .…”
Section: Hyperglycemia and Susceptibility To Infectionmentioning
confidence: 99%
“…were exposed to high glucose levels [162] or dextrose octreotide. [163] This study demonstrates that glucose exposure dampened IL-2, IL-6 and IL-10 levels in a concentration-dependent manner while conversely inducing the expression of TGF-β1 which may explain immune failure. [162] Increased glycation leads to a reduction of IL-10 secretion by myeloid cells.…”
Section: Review Articlementioning
confidence: 67%